Integration of Swot-Balance Scorecard to Formulate Strategic Planning in the Technology and Vocational Education in Indonesia - Suharno, Dr (Journal of Technical Education and Training, 2016)
This paper describes the method of preparation of a comprehensive strategic planning model for technology and vocational education. For this purpose, the quantitative SWOT method has been utilizedilizes been usebeen used and incorporated with the Balanced Score Card. The steps taken during this study were: first, conducting a SWOT analysis quantitatively; second, using the Balanced Score Card to define the strategic issues and to decide the successful procedure. The object of this study was the Mechanical Engineering Education (MEE) Study Programme and Civil Engineering Education (CEE) of Sebelas Maret University in Indonesia. SWOT quantitative analysis was conducted on 124 respondents. Respondents embrace the design team study programs, university policymakers, alumni, and students. The result shows that SWOT methodology integrated with the Balanced Score Card are often used effectively to easier the precise strategic problems. Supported by these strategic challenges, the design team will quickly formulate the strategic development of every study programme.